Life on the Line: One Woman's Tale of Work, Sweat, and Survival - De Santis, Solange (Penguin Random House Canada, 1999)
Just when Solange De Santis had achieved success and security in the white-collar world of journalism, she decided to leave it all to work on the line during the final year and a half of a General Motors van plant in Scarborough, Ontario. --Publisher's description
Keywords: Assembly Line; Automotive; Blue-collar work; Gender; Journalist; Ontario Scarborough; Pink-collar work